Microbial Landscape and Antimicrobial Therapy of Sepsis/Septic Shock in Children and Neonates (Herald of the National Children's Medical Center, 2025)
Aim. To present an overview of current approaches to antimicrobial therapy for sepsis and septic shock in children and neonates, based on international guidelines and the microbiological characteristics of the pediatric population.Materials and methods. A systematic review of scientific literature from the past 10–15 years was conducted using PubMed, eLibrary, Google Scholar, and ScienceDirect databases. The analysis focused on pediatric sepsis, antimicrobial therapy, and intensive care. Particular emphasis was placed on the Surviving Sepsis Campaign (2020–2021) guidelines and findings from major multicenter studies.Results. The etiological profile of pediatric sepsis varies by age and underlying conditions. Gram- negative and gram-positive bacteria remain predominant pathogens, with an increasing prevalence of resistant strains. Early initiation of antibiotic therapy (within 1–3 hours) is associated with improved clinical outcomes. Empirical therapy should be broad-spectrum initially, followed by de-escalation guided by microbiological data. Special attention must be paid to the individualization of dosage and treatment duration.Conclusion. Blood culture remains the primary diagnostic tool for sepsis, although the absence of bacteremia does not exclude the diagnosis when clinical and laboratory criteria are present. A single positive culture identifying pathogens such as Staphylococcus aureus (MRSA), Streptococcus pneumoniae, Klebsiella pneumoniae, Pseudomonas aeruginosa, Acinetobacter baumannii, or fungi is sufficient for confirmation. Timely initiation of antibiotic therapy—ideally within one hour of diagnosis—should be the goal for children with septic shock. For patients without overt signs of shock, antimicrobial therapy should be initiated as early as possible, with a diagnostic window of up to three hours. Decisions on continuation, narrowing, or discontinuation of therapy should be guided by clinical judgment and indirect evidence, taking into account the infection site, risk factors, and adequacy of clinical improvement.
Keywords: pediatric sepsis; neonatal sepsis; prognostic criteria; antimicrobial strategy; intensive care; biomarkers; targeted antimicrobial therapy